Certain dark things ebook A novel. - Moreno-Garcia, Silvia (Tor Nightfire, 2021)
From Silvia Moreno-Garcia, the New York Times bestselling author of Mexican Gothic , comes Certain Dark Things , a pulse-pounding neo-noir that reimagines vampire lore. Welcome to Mexico City, an oasis in a sea of vampires. Domingo, a lonely garbage-collecting street kid, is just trying to survive its heavily policed streets when a jaded vampire on the run swoops into his life. Atl, the descendant of Aztec blood drinkers, is smart, beautiful, and dangerous. Domingo is mesmerized. Atl needs to quickly escape the city, far from the rival narco-vampire clan relentlessly pursuing her. Her plan doesn't include Domingo, but little by little, Atl finds herself warming up to the scrappy young man and his undeniable charm. As the trail of corpses stretches behind her, local cops and crime bosses both start closing in. Vampires, humans, cops, and criminals collide in the dark streets of Mexico City. Do Atl and Domingo even stand a chance of making it out alive? Or will the city devour them all? At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.